Instrumental requirements for the study of Venus' cloud top using the UV imaging spectrometer VeSUV. Issue 1 (1st July 2021) - Marcq, Emmanuel; Montmessin, Franck; Lasue, Jérémie; Bézard, Bruno; Jessup, Kandis L.; Lee, Yeon Joo; Wilson, Colin F.; Lustrement, Benjamin; Rouanet, Nicolas; Guignan, Gabriel
Abstract: Ultraviolet spectral imaging has been a powerful tool to investigate the cloud top of Venus, allowing for measurement of several minor gases (especially SO2, SO, O3 ), of cloud top aerosol's microphysical properties and of atmospheric dynamics through tracking of the unevenly distributed UV absorber. After a brief review of recent UV instruments that orbited around Venus, we present the results of a state-of-the-art radiative transfer model from Marcq et al. (2020) to derive the spectral resolution and Signal-to-Noise ratio (SNR) required to derive abundances of these gases, retrieve optical properties of the aerosols beyond our current knowledge. This leads us to propose a two-channel UV hyperspectral push-broom imager called VeSUV (standing for Venusian Spectroscopy in UV) whose technical characteristics will improve on existing measurements by a factor of at least 2, and which is well suited to the integration into the payload of future low Venus orbit platforms such as the proposed EnVision mission to ESA M5 call.